Nghiên cứu khâu mạch quang hóa của hệ khâu mạch quang trên cơ sở nhựa epoxy biến tính dầu trẩu. Phần III. - Hiền và cộng sự, Lê Xuân (Vietnam Journal of Chemistry, 2014)
The photopolymerization of epoxy group in the 20 mm thick film of the system containing 5% triarylsulfonium salt (TAS) and epoxy resin modified by tung oil (ETT39), monome epoxy cyracure 6105 (BCDE) with different mass ratios ETT39/BCDE 10/90, 30/70, 50/50, 70/30 have been studied. The fastest rate of the reaction was observed in the system with the weight ratio ETT39/BCDE = 50/50 leading to epoxy conversion of the ETT39 and BCDE 82% and 98% respectively after 8.4 seconds exposure under 250 mW/cm2 intensity UV-lamp. The influence of the film thickness studied in range from 10 mm to 50 mm showed the decrease of the photocrosslinking rate with the increase of the film thickness.